High tc superconductors - Bongers, P. F.; Schlenker, C.; Stritzker, B. (European Materials Research Society symposia proceedings, 1989)
The papers in this two volume set provide the latest information on research and development in the field of high Tc-materials. Special emphasis is placed on methods of preparation and microstructural characterization for both thin films and single crystals. Considerable attention is also paid to the potential applications of thin films and bulk materials. The following topics are covered in detail: New superconductors; Relations between structure and/or substitution and superconductivity in ternary Cu-oxides; Single crystals, microstructure; Thin films, preparation and properties; Technical applications.